The relationship between negative emotions and consumer complaint intention following clothing retailers’ in-store service failures - Jacobs, B.M. (Bertha Margaretha) (University of Pretoria, 2021)
Dissertation (MSc Consumer Science (Clothing Retail Management))--University of Pretoria, 2020.